Experimental Design and Interpretation of Terrestrial Ecosystem Studies Using 15N Tracers: Practical and Statistical Considerations - Schleppi, Patrick; Wessel, Wim W. (Frontiers in Environmental Science, 2021)
The stable isotope 15N is an extremely useful tool for studying the nitrogen (N) cycle of terrestrial ecosystems. The affordability of isotope-ratio mass spectrometry has increased in the last decades and routine measurements of δ15N with an accuracy better than 1‰ are now easily achieved. Except perhaps for wood, which has a very high C/N ratio, isotope analysis of samples is, thus, no longer the main challenge in measuring the partitioning of 15N used as tracer in ecosystem studies. The central aim of such experiments is to quantitatively determine the fate of N after it enters an ecosystem, mainly as fertilizer, as atmospheric deposition or as plant litter. By measuring how much of this incoming N goes into different ecosystem pools, inferences can be made about the entire N cycle. Sample collection and preparation can be tedious work. Optimizing sampling schemes is thus an important aspect in the application of 15N in ecosystem research and can be helpful for obtaining a high precision of the results with the available manpower and budget. In this contribution, we combine statistical and practical considerations and give recommendations for the design of labeling experiments and also for assessments of natural 15N abundance. In particular, we discuss soil, vegetation and water sampling. We additionally address the most common questions arising during the calculation of tracer partitioning, and we provide some examples of the interpretation of experimental results.